New-Generation Active Videogaming Maintains Energy Expenditure in Children Across Repeated Bouts - Rosenberg, M.; Lay, B.; Lee, M.; Derbyshire, A.; Kur, J.; Ferguson, R.; Maitland, C.; Mills, A.; Davies, C.; Pratt, Steve; Braham, R. (Mary Ann Liebert, Inc Publishers, 2013)
© Copyright 2013, Mary Ann Liebert, Inc. 2013.Objective: Active videogames (AVGs) remain popular among 10-15-year-old children. The Xbox 360 Kinect™ from Microsoft (Redmond, WA) represents a new generation of AVGs where body movements are used to control gameplay. The purpose of this study was to measure energy expenditure required to play repeated bouts of six Microsoft Xbox 360 Kinect games ("Motion Sports Adrenaline™," "Sonic Free Riders™," "Virtua Tennis 4™," "Kinect Sports™," "Kinect Adventures™," and "Just Dance 3™"). Subjects and Methods: Forty-seven children (between 10 and 15 years) participated in a repeated-measures experiment, completing five 1-hour sessions (one familiarization and four separate gaming sessions). Three different AVGs were played for 15 minutes during each gaming session in a counterbalanced order. An Actiheart (CamNtech Ltd., Cambridge, United Kingdom) was used to monitor heart rate and acceleration during gameplay. Results: Average energy expended across the six AVGs during 15 minutes of gameplay was 3.0±0.17 metabolic equivalents/minute, significantly higher than resting energy expenditure (P<0.01). Similar levels of energy expenditure were observed between the first and fourth gaming session for all six games, although the energy expenditure between each game over the four sessions was similar. Boys expended more energy than girls within each AVG and across the four gaming sessions. Conclusions: The Microsoft Xbox 360 Kinect games in this study were found to elicit moderate-intensity exercise over four gaming sessions, with no decay in energy expenditure over several gaming sessions. Although small differences in the energy expenditure between the six Microsoft Xbox Kinect games were found, they are all likely to contribute toward reduced sitting time in children.